Epigenome-wide DNA methylation association study of CHIP provides insight into perturbed gene regulation - Kirmani, Sara; Huan, Tianxiao; Van Amburg, Joseph C.; Joehanes, Roby; Uddin, Md Mesbah; Nguyen, Ngoc Quynh H.; Yu, Bing; Brody, Jennifer A.; Fornage, Myriam; Bressler, Jan; Sotoodehnia, Nona; Ong, David A.; et al. (Nature communications, 2025)
With age, hematopoietic stem cells can acquire somatic mutations in leukemogenic genes that confer a proliferative advantage in a phenomenon termed CHIP. How these mutations result in increased risk for numerous age-related diseases remains poorly understood. We conduct a multiracial meta-analysis of EWAS of CHIP in the Framingham Heart Study, Jackson Heart Study, Cardiovascular Health Study, and Atherosclerosis Risk in Communities cohorts ( N = 8196) to elucidate the molecular mechanisms underlying CHIP and illuminate how these changes influence cardiovascular disease risk. We functionally validate the EWAS findings using human hematopoietic stem cell models of CHIP. We then use expression quantitative trait methylation analysis to identify transcriptomic changes associated with CHIP-associated CpGs. Causal inference analyses reveal 261 CHIP-associated CpGs associated with cardiovascular traits and all-cause mortality (FDR adjusted p -value < 0.05). Taken together, our study reports the epigenetic changes impacted by CHIP and their associations with age-related disease outcomes. In CHIP, somatic mutations in a hematopoietic stem cell lead to a clonal subpopulation of blood cells. Here, the authors perform a CHIP meta-EWAS to establish its epigenetic features and age-related outcomes.